Revealing Network Structure, Confidentially: Improved Rates for Node-Private Graphon Estimation - Borgs, Christian; Chayes, Jennifer; Smith, Adam; Zadik, Ilias (2018)
Motivated by growing concerns over ensuring privacy on social networks, we develop new algorithms and impossibility results for fitting complex statistical models to network data subject to rigorous privacy guarantees. We consider the so-called node-differentially private algorithms, which compute information about a graph or network while provably revealing almost no information about the presence or absence of a particular node in the graph.